Mineral Composition of Some Kabuli Chickpea (Cicer arietinum L.) Cultivars Leaves - TURAN, METIN; ELKOCA, ERDAL (Asian Journal of Chemistry, 2010)
In this paper, the leaf mineral concentrations of ten nationally registered Kabuli type chickpea cultivars were characterized. Young, fully expanded leaves (fourth thorough seventh nodes from apex) were harvested at both early (30 d after emergence) and late (55 d after emergence) vegetative stages. The leaves were dried, ashed and analyzed for mineral concentrations. In general, N, P, K, Ca, Fe, Mn and Zn contents of chickpea plants were higher than those of common leafy vegetables such as spinach, radish, pepper, lettuce, cabbage, broccoli and celery. No major differences were observed in leaf mineral concentrations among the Kabuli type chickpea cultivars. Mineral concentrations were generally lower in leaves collected at the later harvest date except for P content of plants. Overall, chickpea leaves were found to be a good source of several minerals required for humans. Most of these leaf mineral contents significantly exceed those previously reported for common leafy vegetables.